Morphological, Mechanical, and Thermal Characterization of Poly(Lactic Acid)/Cellulose Multifilament Fibers Prepared by Melt Spinning. Issue 4 (13th October 2016) - Aouat, Tassadit; Kaci, Mustapha; Devaux, Eric; Campagne, Christine; Cayla, Aurélie; Dumazert, Loic; Lopez‐Cuesta, José‐Marie
Abstract: In this study, multifilament fibers based on neat poly(lactic acid) (PLA), PLA/cellulose nanowhiskers (CNWs), and PLA/cellulose microcrystalline (MCC) loaded at 1 and 3 wt.% were prepared by melt‐spinning process in the presence of PLA‐grafted maleic anhydride (PLA ‐g‐ MA) used as the compatibilizer and PEG as the plasticizer. This study showed that the incorporation of MCC in PLA matrix whatever the loading rate was not suitable for multifilament fibers spinning compared with CNW, due to the restricted drawability and a poor dispersion of the MCC within the PLA matrix. Furthermore, the whole characterization studies indicated that the incorporation of 1 wt.% of CNW in PLA with addition of the compatibilizer led to better thermal stability, flame retardancy, and multifilament tensile properties compared with neat PLA and with other filled PLA multifilament fibers.